Study On Improving The Acoutics Performance Of Masjid Sayyidina Abu Bakar UTeM - Kassim, Dg Hafizah (2016)
It has been known that the ‘acoustics design’ in most of mosques around the world is often neglected in the early design stage of the building. As a consequence, acoustics performance inside mosques is usually poor. The case includes the Sayyidina Abu Bakar Mosque in UTeM where poor speech intelligibility is experienced during congregation. The main objectives of this work are to investigate the root cause of the acoustic problem and to propose acoustic treatment to improve the acoustic quality inside the mosque. The latter is conducted through computer simulation. The measurement found that the mosque has considerably high reverberation time (RT60) at frequency below 1 kHz with the highest RT60 of 5.56 s at 500 Hz. The RT60 calculated from simulation is validated with this measured results and from the simulation, other acoustics parameters namely early decay time, clarity, definition and sound transmission index also indicate poor acoustic quality. This is due to the large volume of the mosque, and walls and ceiling mostly consist of reflective surfaces which cause late reflections of sound. These reflections, especially from the inclined roof, contribute to the high RT60 around the front area of the minbar. From simulation, the acoustic treatment using mineral wool absorber with a thickness of 25 mm installed on the inclined roof can reduce the RT60 to 3.25 s at 500 Hz. A Helmholtz resonator-like absorber to counter the problem at low frequency is also simulated using micro-perforated panel (MPP). This is also proposed to give a green absorber compared to the conventional synthetic absorber from fibrous absorber. It is found that installation of MPP on the inclined roof, can give better reduction of RT60 to 2.57 s at 500 Hz. Doubling the MPP separated with air gap is also found to further lower the RT60 to 2.32 s at 500 Hz. Dome shape effect has also been simulated to compare the pyramidal and spherical domes. The former is found to be the identical dome shape of mosques in Malacca, Malaysia. The study reveals that the pyramidal dome provides better acoustics performance compared to that of the spherical dome.